Molten attachment removing method for neodymium iron boron laser cutting and protective agent
By forming a dense protective film on the surface of NdFeB material and removing adhesions in the electroplating process, the problem of melt adhesion during laser cutting is solved, material corrosion and magnetic loss are avoided, and efficient and environmentally friendly product treatment is achieved.
Patent Information
- Application Number
- CN202411759148.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the laser cutting process of neodymium iron boron materials, the melt is not easy to clean up, and the special nature of the protective agents on the market may not be considered sufficiently, which may lead to rust on the surface of the material or the magnetic properties.
A protective agent formula, including deionized water, white mineral oil, anti-splash agent, anti-rust agent, aqueous polyurethane emulsion resin and talc powder, forms a dense protective film that prevents the adhesion of melts by soaking and drying, and The protective film is removed by using nitric acid washing in the electroplating process.
Effectively isolate molten splashes, prevent corrosion and magnetic properties on the surface of neodymium iron boron products, ensure product appearance quality and magnetic properties, and protectant is environmentally friendly, low-cost and safe to use.
Smart Images

Figure CN119221059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB product processing, and in particular to a method for removing molten deposits for NdFeB laser cutting and a protective agent. Background Art
[0002] As a high-performance permanent magnet material, NdFeB has the characteristics of high remanence density, high coercivity and high magnetic energy product and is widely used in many fields. However, it is easy to rust and oxidize in a humid, acidic or alkaline environment, which reduces its magnetic properties.
[0003] As an efficient and precise processing method, laser cutting plays an important role in the processing of NdFeB materials. Laser cutting uses a high-power density laser beam to scan the surface of the material, heats the material to several thousand degrees Celsius in a very short time, melts or vaporizes the material, and then uses high-pressure gas to blow the molten or vaporized material away from the cutting seam to achieve the purpose of cutting the material. However, the high-temperature molten metal splashes generated during the laser cutting process are easy to adhere to the surface of the material, affecting the appearance quality of the final product.
[0004] Existing solutions to the problem of melt adhesion during laser cutting, such as adjusting laser cutting parameters, adding external mechanical devices for dust extraction or vacuum adsorption, are effective to a certain extent, but these methods are not applicable to thin, small, and high-precision NdFeB magnetic products. In addition, the use of protective agents is also a common practice, but most of the protective agents on the market are designed for metal welding, and the particularity of NdFeB materials is not considered enough. Improper use may cause rust on the surface of the material or affect the magnetism. Summary of the invention
[0005] The purpose of the present invention is to provide a method for removing molten deposits during NdFeB laser cutting, which can effectively solve the problem that the molten deposits are difficult to clean during the laser cutting of NdFeB, and can also ensure that the surface of the NdFeB product is not corroded and the magnetic properties are not affected.
[0006] To achieve the above object, the solution of the present invention is: a method for removing molten deposits for NdFeB laser cutting, comprising the following steps: Step 1: Prepare protective agent: weigh the raw materials according to the following weight percentages: Deionized water 50~65%, white mineral oil 5~7%, anti-splash agent 13~15%, rust inhibitor 2~5%, penetrant 2~3%, water-based polyurethane emulsion resin 5~7%, talcum powder 5~8%, water-based full synthetic agent 3~5%, stir and mix all the raw materials in deionized water to form a protective agent solution; The water-soluble rust inhibitor includes, by weight percentage, 10-15% triethanolamine borate, 10-15% methyl isopropyl ketone, 10-20% xylene, 5-10% calcium oxide, 5-10% epoxy resin, and 30-60% deionized water; Step 2: Clean the NdFeB product to be cut to remove surface impurities; Step 3: Soak the cleaned NdFeB product in the prepared protective agent solution for 1 to 2 minutes to ensure that the surface of the NdFeB product is fully in contact with the protective agent solution; Step 4: Dry the soaked NdFeB product at a temperature of 65-75°C to solidify the protective agent on the surface to form a dense and uniform solid protective film; Step 5: Laser cutting the dried NdFeB product; Step 6: Electroplating the NdFeB products after laser cutting. During the electroplating pretreatment process, first use 2~4% nitric acid to pickle the NdFeB products for 5~8s to dissolve the protective film on its surface, and then use pure water to ultrasonically rinse the NdFeB products to remove the nitric acid on its surface, the dissolved protective film and the molten material.
[0007] Furthermore, the water-based full synthetic agent is prepared by mixing ethylene glycol and polyacrylamide in a mass ratio of 2 to 3:1; Furthermore, the anti-splash agent is prepared by mixing a high molecular polymer and an activator at a mass ratio of 2 to 3:1, and the high molecular polymer is one of polyvinyl alcohol, polyacrylamide and polyvinyl pyrrolidone.
[0008] Furthermore, the main components of the penetrant include higher fatty alcohols, polyoxyethylene and polyoxypropylene.
[0009] Furthermore, in step 4, the soaked NdFeB product is driven by a conveyor belt and dried in a tunnel furnace. The conveyor belt runs at a speed of 0.5 m / min and the drying time is 4 min.
[0010] Furthermore, the protective agent comprises the following components by weight percentage: 55% deionized water, 7% white mineral oil, 14% anti-splash agent, 3% rust inhibitor, 2% penetrant, 7% water-based polyurethane emulsion resin, 8% talcum powder, and 4% water-based full synthetic agent.
[0011] The present invention also provides a protective agent for removing molten deposits for NdFeB laser cutting, which comprises the following components by weight percentage: 50-65% of deionized water, 5-7% of white mineral oil, 13-15% of anti-splash agent, 2-5% of rust inhibitor, 2-3% of penetrant, 5-7% of waterborne polyurethane emulsion resin, 5-8% of talcum powder, and 3-5% of water-based full synthetic agent, wherein the raw materials are stirred and mixed in deionized water to form a protective agent solution; The water-soluble rust inhibitor comprises, by weight percentage, 10-15% triethanolamine borate, 10-15% methyl isopropyl ketone, 10-20% xylene, 5-10% calcium oxide, 5-10% epoxy resin, and 30-60% deionized water.
[0012] Furthermore, the water-based full synthetic agent is prepared by mixing ethylene glycol and polyacrylamide in a mass ratio of 2 to 3:1; The anti-splash agent is prepared by mixing a high molecular polymer and an activator in a mass ratio of 2 to 3:1, wherein the high molecular polymer is one of polyvinyl alcohol, polyacrylamide and polyvinyl pyrrolidone; The main components of the penetrant include higher fatty alcohols, polyoxyethylene and polyoxypropylene.
[0013] After adopting the above scheme, the beneficial effects of the present invention are: 1. The protective agent provided by the present invention can form a dense protective film on the surface of NdFeB products, which can effectively isolate the molten spatter generated during laser cutting, prevent the spatter from directly contacting the surface of NdFeB products and affecting the appearance quality of the products, and fundamentally solve the problem of molten material adhesion and difficulty in cleaning during laser cutting of NdFeB.
[0014] 2. Compared with the existing protective agents on the market that contain high concentrations of hydrochloric acid, nitric acid, and phosphoric acid, the protective agent of the present invention uses triethanolamine borate as an anti-rust component, uses methyl isopropyl ketone and xylene to adjust the solvent performance, adds calcium oxide to enhance stability, and incorporates epoxy resin to improve the toughness and adhesion of the protective film. Through this series of ratios, a protective agent that does not contain high-concentration acid-type substances is obtained, so it will not cause additional corrosion risks to the NdFeB material during use, and effectively avoids the phenomenon of reducing the magnetic moment of the NdFeB material due to rust.
[0015] 3. After the protective agent is applied to the surface of the NdFeB product, it is dried at 65~75℃ to form a protective film. The drying temperature is appropriate and will not cause demagnetization of the product.
[0016] 4. The protective film formed by the protective agent can be removed by pickling and cleaning with 2%~4% nitric acid in the subsequent electroplating process pretreatment, thus ensuring the cleanliness of the product surface.
[0017] In addition, the protective agent solution of the present invention is environmentally friendly and non-toxic, and will not cause harm to the environment and human body when used. At the same time, the cost of the protective agent is relatively low, and 1L of the solution can be applied to about 800-1000 NdFeB magnetic sheets that have not been laser cut, which is cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Flow chart of the method for removing molten deposits for NdFeB laser cutting of the present invention; Figure 2 This is a schematic diagram of the molten material attached to the surface of the NdFeB product without protective agent after laser cutting; Figure 3 This is a schematic diagram showing that the surface of the NdFeB product without protective agent is still attached with molten material after electroplating; Figure 4 Schematic diagram of the corrosion on the surface of NdFeB magnets after applying the protective agent available on the market; Figure 5 It is a schematic diagram of the surface of a NdFeB magnet after being coated with the protective agent of the present invention and subjected to laser cutting and electroplating treatment. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The present invention provides a method for removing molten deposits for NdFeB laser cutting, comprising the following steps (refer to the process Figure 1 ): Step 1: Prepare protective agent: weigh the raw materials according to the following weight percentages: Deionized water 50~65%, white mineral oil 5~7%, anti-splash agent 13~15%, rust inhibitor 2~5%, penetrant 2~3%, water-based polyurethane emulsion resin 5~7%, talcum powder 5~8%, water-based full synthetic agent 3~5%, stir and mix the raw materials in deionized water to form a protective agent solution. Among them, deionized water is used as a solvent to dilute and dissolve the various components. The molecular structure of white mineral oil has lipophilicity and hydrophobicity, which can quickly migrate the moisture on the surface of the NdFeB magnetic sheet to the gas-liquid interface, reduce the surface tension of the liquid, and prevent the NdFeB magnetic sheet from laminating due to water tension in the solution. The water-based polyurethane emulsion resin has good stability and dispersibility, and can form a tough and wear-resistant film. Talc can adsorb some substances around its particles to make them evenly dispersed, increase the contact surface with deionized water, and accelerate the dissolution of substances in the solution. At the same time, talc has good adsorption capacity, which can adsorb the moisture and grease of the NdFeB magnetic sheet after soaking and accelerate surface drying.
[0021] The protective agents currently available on the market usually contain high concentrations of hydrochloric acid, nitric acid, and phosphoric acid. High concentrations of acid will react with the rare earth elements and iron elements in the NdFeB material, which will not only corrode the surface of the product and affect its finish, but also affect its magnetic properties. Figure 4 As shown in the figure, after applying the protective agent available on the market, the surface of the NdFeB magnet showed obvious corrosion and rust.
[0022] In this case, in order to address the shortcoming of NdFeB materials being very easy to corrode and rust, a water-soluble rust inhibitor was first configured. The water-soluble rust inhibitor, measured by weight percentage, includes 10-15% triethanolamine borate, 10-15% methyl isopropyl ketone, 10-20% xylene, 5-10% calcium oxide, 5-10% epoxy resin, and 30-60% deionized water. Among them, a water-soluble rust inhibitor containing triethanolamine borate is used. The main component of the triethanolamine borate rust inhibitor is triethanolamine borate, which does not contain high concentrations of acid-type substances. It can form a dense protective film on the metal surface and has the characteristics of high temperature resistance, high humidity, and high salt resistance. The methyl isopropyl ketone helps to improve the fluidity and permeability of the rust inhibitor, so that the rust inhibitor can be more evenly covered on the surface of the material. Xylene helps the active ingredients in the rust inhibitor to dissolve and disperse better. It can also increase the volatility and drying speed of the rust inhibitor, thereby shortening the processing time. Calcium oxide, as an alkaline substance, can neutralize possible trace acidic substances to prevent them from corroding the material. Epoxy resin can form a tough and dense protective film on the surface of the material. By rationally matching the above ingredients, a water-soluble rust inhibitor specifically for special materials such as NdFeB is prepared.
[0023] The water-based full synthetic agent in the protective agent of the present invention is mixed with ethylene glycol and polyacrylamide in a mass ratio of (2-3):1. The water-based full synthetic agent is used as a solvent for the organic synthesis and catalysis of the solution. The anti-splash agent is mixed with a high molecular polymer and an activator in a mass ratio of (2-3):1, and the high molecular polymer is one of polyvinyl alcohol, polyacrylamide and polyvinyl pyrrolidone. The anti-splash agent can form an isolation film on the surface of the NdFeB magnetic sheet before laser processing, so that the molten metal particles generated during laser cutting cannot directly contact the product surface. The main components of the penetrant include higher fatty alcohols, polyoxyethylene and polyoxypropylene. The penetrant used in this scheme is purchased from Tongxiang Henglong Chemical Co., Ltd. The penetrant can improve the wettability of the solution, reduce its surface tension, and make it easier to contact and mix with the NdFeB magnetic sheet that needs to be immersed in the solution.
[0024] Step 2: Clean the NdFeB product to be cut to remove the oil stains and magnetic powder on the surface during the processing. This case takes the NdFeB magnetic sheet with a size of 50.2mm×48.5mm and a thickness of 0.4mm as an example to illustrate the processing of the product, but it is not limited to this size; Step 3: Soak the cleaned NdFeB magnetic sheets in the prepared protective agent solution for 1 to 2 minutes, so that both sides of the product are fully in contact with the protective agent solution to ensure that the protective film finally formed on the product can protect the product without omissions. Here, too long an immersion time will lead to excessive penetration of the protective agent, which may cause the protective film on the surface of the product to be too thick, brittle, or produce unnecessary internal stress, affecting the physical properties and magnetic properties of the product; while too short an immersion time may cause the protective agent to fail to fully cover the surface of the product, resulting in poor protection effect, and some areas may not form an effective protective film, thereby increasing the risk of rust and reduced magnetic moment of the product.
[0025] Step 4: Dry the soaked NdFeB magnetic sheets, specifically by using a conveyor belt to drive the product through a tunnel furnace, with a drying temperature of 65~75°C (preferably 70°C). This drying temperature is suitable for ensuring the effective curing of the protective film and ensuring that it forms a stable and dense protective layer on the surface of the product, while avoiding the adverse effects of excessive temperature on the product, such as causing product demagnetization and other unfavorable conditions. This embodiment takes a tunnel furnace with a length of 2m as an example, the conveyor belt runs at a speed of 0.5m / min, and the heating time is about 4min. The protective agent is heated to quickly form a dense protective film on the surface of the product.
[0026] Step 5: Place the dried NdFeB magnetic sheets neatly in the silo of the laser cutting equipment for laser cutting into rectangular blocks with a size of 8.2mm×7.5mm. The cut products fall into the receiving box through the unloading device. Step six, subject the laser-cut NdFeB magnetic sheets to electroplating. During the electroplating pretreatment process, first use 3% nitric acid as a pickling agent, and ultrasonically pickle the NdFeB magnetic sheets. The pickling time is 5 to 8 seconds. The pickling time should not be too long, as it may cause the size of the NdFeB product to decrease. Proper pickling can dissolve the protective film on the surface of the NdFeB magnetic sheets. This is because some substances in the solution, such as white mineral oil, talcum powder, calcium oxide and xylene in the rust inhibitor, polyethylene in the anti-splash agent, and polyacrylamide in the water-based full synthetic agent, can react with nitric acid to dissolve the protective film. At the same time, the molten material attached to the surface of the protective film detaches as the protective film detaches from the surface of the NdFeB magnetic sheet. Then, the NdFeB magnetic sheet is ultrasonically rinsed with pure water to remove the nitric acid, dissolved protective film, and molten material on its surface, so as to purify the surface of the product. The final cleaning result is as follows: Figure 5 As shown, there is no molten material attached to the surface of the product and there is almost no rust or corrosion.
[0027] Experimental Example 1: This experimental example uses examples and comparative examples to illustrate the effects of applying a protective agent and the ratio of the components in the protective agent on the yield rate of NdFeB magnetic sheets after laser cutting and electroplating.
[0028] The distribution ratios of the protective agents in the embodiments and comparative examples are shown in Table 1: Table 1
[0029] It can be seen from Table 1 that the protective agent in Examples 1-3 can form a dense protective film on the surface of the product, and the protective agent has almost no corrosion to the surface of the product. Figure 5 , and after laser cutting and electroplating, there is almost no molten material attached to the product surface, and the defective rate of molten material attached to the finished product is kept at a low level.
[0030] Although the protective film formed by the protective agent in Comparative Example 1-2 still maintains a certain density, the rust corrosion rate of the product and the defective rate of the finished product molten attachment are increased due to the improper proportion of the rust inhibitor, water-based polyurethane emulsion resin and other components.
[0031] In Comparative Example 3, since the proportion of rust inhibitor, penetrant and aqueous polyurethane emulsion resin is too low, the solution concentration required to form a protective film is reduced, and the protective effect of the solution is reduced, resulting in reduced density of the protective film and poor protection effect. During the laser cutting process of the dried product, the high-temperature melt will melt the thinner protective film and adhere to the surface of the material, and the defective rate of the finished product molten attachment is significantly increased.
[0032] In Comparative Example 4, since no protective agent was used, the product surface was not protected by a protective film, and a large amount of molten material was attached to the product surface. Figure 3 As shown, the defective rate of finished products is high.
[0033] Experimental Example 2: This experimental example follows the ratio of the protective agent in Example 2 to study the effect of the ratio of each component in the rust inhibitor on the surface morphology of the NdFeB magnetic sheet.
[0034] Table 2
[0035] It can be seen from Table 2 that the protective agent prepared from the rust inhibitors of Examples 4-6 hardly causes corrosion to the surface of the NdFeB product.
[0036] The protective agent prepared from the rust inhibitor of Comparative Example 4 has insufficient rust prevention effect due to the low content of triethanolamine borate, calcium oxide and epoxy resin, resulting in corrosion and rust on the surface of the NdFeB product.
[0037] The protective agent prepared from the rust inhibitor of Comparative Example 5 has too high content of triethanolamine borate, calcium oxide and epoxy resin; the protective agent prepared from the rust inhibitor of Comparative Example 6 has too high content of triethanolamine borate and calcium oxide. The protective agents finally prepared from the rust inhibitors of these two comparative examples have inadequate addition of some components, resulting in insufficient dissolution, solute precipitation to form precipitates attached to the surface of the NdFeB magnetic sheet, and ultimately reducing the density of the protective film and slowing the film formation speed.
[0038] To further illustrate various embodiments, the present invention provides drawings. These drawings are part of the disclosure of the present invention, which are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments.
[0039] The above description is only a preferred embodiment of the present invention and is not a limitation on the design of this case. Any equivalent changes made based on the design key of this case shall fall within the protection scope of this case.
Claims
1. A method for removing molten deposits for NdFeB laser cutting, characterized in that: The steps include: Step 1: Prepare protective agent: weigh the raw materials according to the following weight percentages: Deionized water 50~65%, white mineral oil 5~7%, anti-splash agent 13~15%, rust inhibitor 2~5%, penetrant 2~3%, water-based polyurethane emulsion resin 5~7%, talcum powder 5~8%, water-based full synthetic agent 3~5%, stir and mix all the raw materials in deionized water to form a protective agent solution; The water-soluble rust inhibitor includes, by weight percentage, 10-15% triethanolamine borate, 10-15% methyl isopropyl ketone, 10-20% xylene, 5-10% calcium oxide, 5-10% epoxy resin, and 30-60% deionized water; Step 2: Clean the NdFeB product to be cut to remove surface impurities; Step 3: Soak the cleaned NdFeB product in the prepared protective agent solution for 1 to 2 minutes to ensure that the surface of the NdFeB product is fully in contact with the protective agent solution; Step 4: Dry the soaked NdFeB product at a temperature of 65-75°C to solidify the protective agent on the surface to form a dense and uniform solid protective film; Step 5: Laser cutting the dried NdFeB product; Step 6: Electroplating the NdFeB products after laser cutting. During the electroplating pretreatment process, first use 2~4% nitric acid to pickle the NdFeB products for 5~8s to dissolve the protective film on its surface, and then use pure water to ultrasonically rinse the NdFeB products to remove the nitric acid on its surface, the dissolved protective film and the molten material.
2. A method for removing molten deposits for NdFeB laser cutting as claimed in claim 1, characterized in that: The water-based full synthetic agent is prepared by mixing ethylene glycol and polyacrylamide in a mass ratio of 2 to 3:
1.
3. A method for removing molten deposits for NdFeB laser cutting as claimed in claim 1, characterized in that: The anti-splashing agent is prepared by mixing a high molecular polymer and an activator in a mass ratio of 2 to 3:1, and the high molecular polymer is one of polyvinyl alcohol, polyacrylamide and polyvinyl pyrrolidone.
4. A method for removing molten deposits for NdFeB laser cutting as claimed in claim 1, characterized in that: The main components of the penetrant include higher fatty alcohols, polyoxyethylene and polyoxypropylene.
5. The method for removing molten deposits for NdFeB laser cutting according to claim 1, characterized in that: In step 4, the soaked NdFeB product is driven by a conveyor belt and dried in a tunnel furnace. The conveyor belt runs at a speed of 0.5 m / min and the drying time is 4 minutes.
6. A method for removing molten deposits for NdFeB laser cutting as claimed in claim 1, characterized in that: The protective agent comprises the following components by weight percentage: 55% deionized water, 7% white mineral oil, 14% anti-splash agent, 3% rust inhibitor, 2% penetrant, 7% water-based polyurethane emulsion resin, 8% talcum powder, and 4% water-based full synthetic agent.
7. A protective agent for removing molten deposits for NdFeB laser cutting, characterized in that: The invention comprises the following components by weight percentage: 50-65% deionized water, 5-7% white mineral oil, 13-15% anti-splash agent, 2-5% rust inhibitor, 2-3% penetrant, 5-7% waterborne polyurethane emulsion resin, 5-8% talcum powder, 3-5% water-based full synthetic agent, and the raw materials are stirred and mixed in deionized water to form a protective agent solution; wherein the water-soluble rust inhibitor comprises by weight percentage 10-15% triethanolamine borate, 10-15% methyl isopropyl ketone, 10-20% xylene, 5-10% calcium oxide, 5-10% epoxy resin, and 30-60% deionized water.
8. The protective agent for removing molten deposits for NdFeB laser cutting according to claim 7, characterized in that: The water-based full synthetic agent is prepared by mixing ethylene glycol and polyacrylamide in a mass ratio of 2 to 3:1; The anti-splash agent is prepared by mixing a high molecular polymer and an activator in a mass ratio of 2 to 3:1, and the high molecular polymer is one of polyvinyl alcohol, polyacrylamide and polyvinyl pyrrolidone; The main components of the penetrant include higher fatty alcohol, polyoxyethylene and polyoxypropylene.
Citation Information
Patent Citations
Composite liquid for electric arc electrochemical machining of aerospace engine parts
CN113667528A
Anti-splashing laser soldering paste and preparation method thereof
CN118789159A
